Response Measurements on an Echinodome Subjected to Explosive Loading - K.M.M. El-Deeb; R. Royles (Shock and Vibration)
Free field explosion experiments were carried out to determine the general characteristics of the pressure pulse generated by a detonator underwater. An echinodome – an axisymmetric shell structure of optimum form – was subjected to a shock wave from the same type of detonator, the structure being in a floating submerged and tethered state. Some indication of the influence of the structure on the incident pressure wave was obtained from a surface mounted miniature pressure gage. Structural response was measured with the aid of strain gages from which principal stress data were deduced. Consideration was given to the theoretical modelling aspects of the problem.